UJI KANDUNGAN LOGAM BERAT TIMBAL (PB) PADA BAYAM (AMARANTHUS SPP) SECARA DESTRUKSI BASAH MENGGUNAKAN SPEKTROSKOPI SERAPAN ATOM (SSA) - Nuryanti (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2018)
Accumulation of heavy metals in the environment increase as effect of industrial activity and technological developments. The potential danger of heavy metal lead (Pb) in the environment and human health has become a major concern for researchers. The spinach is widely distributed and has become a widely consumed vegetable varieties in Indonesia. This plant grows rapidly and widely which can be one of the source of lead (Pb) hyperaccumulator. The analysis of heavy metal lead (Pb) in spinach has been carried out with wet destruction method. Sample of fresh spinach has been taken from Sunter traditional market, North Jakarta. Determination of heavy metal lead (Pb) in red spinach and green spinach were measured using atomic absorption spectroscopy. The analysis showed that red spinach leaves contain lead (Pb) metal of 4.15 ppm and green spinach leaves of 9.75 ppm. When compared with data of the Indonesian national standard (SNI) that is 0.5 ppm indicated that the heavy metal lead (Pb) in red spinach and green spinach exceed the threshold set by SNI